POSSÍVEIS IMPACTOS NA SAÚDE HUMANA DEVIDO A EXCREMENTOS DE CAPIVARAS (HYDROCHOERUS HYDROCHAERIS) - Felipe Zampieri Vieira Batista (2023)
Humans can be exposed to heavy metals from animal feces, particularly in communities where animals live in close proximity to humans. Therefore, there are impacts on human health due to exposure to poorly managed animal feces transmitted by involuntary oral, inhalation and dermal routes. The aim of this study was to quantify metals, metalloids and non-metals in the excrements of capivara (Hydrochoerus hydrochaeris) that live in places like Parque Ecológico Anhandui, Parque Ecológico Sóter, Parque Ecológico Prosa and Lago do Amor, located close to the central region of the city of Campo Grande /MS. The quantification of elements in the excrement samples of the animals were obtained after acid digestion and using an inductively coupled plasma optical emission spectrometer (ICP OES). According to the results, there are significant concentrations of arsenic (As) lead (Pb), cobalt (Co), chromium (Cr), aluminum (Al) cadmium (Cd), nickel (Ni), cobalt (Co), iron (Fe), zinc (Zn), manganese (Mn), magnesium (Mg), selenium (Se), phosphorus (P) and molybdenum (Mo) in the excrements of these animals. There are no statistical differences between the median concentrations of metals in the excrement of animals from different locations. However, higher mean concentrations in mg/Kg of Al (140.322), As (0.010041), Cd (1.042), Cr (26.866), Co (1.946), Cu (50.764), Mn (291.469), Mo (3.634), Ni (5.475), Zn (100.027) and Pb (8.762) were quantified in the excrements of animals living near Lago do Amor. According to the risk assessment, potential risks to the health of adults and children may occur due to the presence of Al, Cd, Co, As, Cu and Mn through involuntary oral ingestion of excrement, via inhalation and dermal. The hazard index due to oral ingestion was HI > 1 for adults and children. Cr, Cu and Pb contractions in capybara excrement are greater than those of other species such as deer. From these results, it is believed that the feces of these animals can be considered as a bioindicator of environmental pollution. However, research considering feeding, as well as the quantification of metals in blood plasma, vegetation on which animals feed in different seasons of the year and locations must be carried out. Studies should be carried out considering populations of these animals that live further away from the Central region of Campo Grande, MS. Keywords: Heavy metals. Capybara. Hydrochoerus hydrochaeris. Public places. Contamination.